Management of the open abdomen: A systematic review with meta-analysis and practice management guideline from the Eastern Association for the Surgery of Trauma. Issue 3 (12th September 2022) - Mahoney, Eric J.; Bugaev, Nikolay; Appelbaum, Rachel; Goldenberg-Sandau, Anna; Baltazar, Gerard A.; Posluszny, Joseph; Dultz, Linda; Kartiko, Susan; Kasotakis, George; Como, John; Klein, Eric
Abstract : Many emergency surgery patients require damage control laparotomy with an open abdomen. The optimal techniques to promote primary myofascial closure are unclear. This Practice Management Guideline reviews the recent literature and suggests fascial traction improve closure rates. Abstract : BACKGROUND: Multiple techniques describe the management of the open abdomen (OA) and restoration of abdominal wall integrity after damage-control laparotomy (DCL). It is unclear which operative technique provides the best method of achieving primary myofascial closure at the index hospitalization. METHODS: A writing group from the Eastern Association for the Surgery of Trauma performed a systematic review and meta-analysis of the current literature regarding OA management strategies in the adult population after DCL. The group sought to understand if fascial traction techniques or techniques to reduce visceral edema improved the outcomes in these patients. The Grading of Recommendations Assessment, Development and Evaluation methodology was utilized, meta-analyses were performed, and an evidence profile was generated. RESULTS: Nineteen studies met inclusion criteria. Overall, the use of fascial traction techniques was associated with improved primary myofascial closure during the index admission (relative risk, 0.32) and fewer hernias (relative risk, 0.11.) The use of fascial traction techniques did not increase the risk of enterocutaneous fistula formation nor mortality. Techniques to reduce visceral edema may improve the rate of closure; however, these studies were very limited and suffered significant heterogeneity. CONCLUSION: We conditionally recommend the use of a fascial traction system over routine care when treating a patient with an OA after DCL. This recommendation is based on the benefit of improved primary myofascial closure without worsening mortality or enterocutaneous fistula formation. We are unable to make any recommendations regarding techniques to reduce visceral edema. LEVEL OF EVIDENCE: Systematic Review and Meta-Analysis; Level IV. Abstract :